The Humanized Care Paradigm: The Chapter of Gilanadhamma Camp - Intawat, Jareerat; Bundasak, Thanapol; Jangasem, Narumol (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
Humanized Care is an identity of the Institute Praboromarajchanok. Humanized Care is holistic caring processes with heart, love, mercy and wishes the clients without any suffer. Humanized Care of the Institute Praboromarajchanok has 3 parts: Service Mind (S), Analytical Thinking (A) and Participation (P). Humanized Care is the important factors that promote holistic caring include 4 dimensions: Physical, Psychological, Social and Spiritual. In this article, the writer points out the humanized care by Gilanadhamma Camp that aims to improvement and development the though process of the students for interesting in life’s authentic and the students can practice with humanized care. The writer infers 5 points: Active listening, Never judge the clients by its cover, Care the clients like family, Smiling and Polite speaking and Willing to practice. The humanized care paradigm can help the students care the clients happily.